Effect of a family-centered clinical intervention on the anxiety of family members of the patients hospitalized in critical care units - F Golaghaie; D Hekmatpou; M Vafaie; M Rafeie; F Rafiei (مجله دانشگاه علوم پزشکی گرگان, 2016)
Background and Objective: Hospitalization of patients in the intensive care units frequently results in anxiety of the family members. This study was performed to investigate the effect of a family-centered clinical intervention on the anxiety of family members of the patients hospitalized in intensive care units.